2021
DOI: 10.3389/fpsyt.2021.753562
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of Marijuana in Mono-Users

Abstract: Marijuana (Cannabis sp.) is among the most recurred controlled substances in the world, and there is a growing tendency to legalize its possession and use; however, the genotoxic effects of marijuana remain under debate. A clear definition of marijuana's genotoxic effects remains obscure by the simultaneous consumption of tobacco and other recreational substances. In order to assess the genotoxic effects of marijuana and to prevent the bias caused by the use of substances other than cannabis, we recruited mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…It has been demonstrated that smoked marijuana, either alone or in combination with tobacco, is capable of inducing genetic damage and cytotoxicity in the cells of the oral mucosa and peripheral blood of consumers. This is evidenced by a study conducted by Souza DV et al, where there was an increase in MNs and KL, as well as by a study carried out by Fabian-Morales E et al, in which genotoxic damage was also demonstrated through an increase in MNs and BUDs [24,55].…”
Section: Effect Of Drug Abuse On the Occurrence Of Nuclear Abnormalitiesmentioning
confidence: 82%
“…It has been demonstrated that smoked marijuana, either alone or in combination with tobacco, is capable of inducing genetic damage and cytotoxicity in the cells of the oral mucosa and peripheral blood of consumers. This is evidenced by a study conducted by Souza DV et al, where there was an increase in MNs and KL, as well as by a study carried out by Fabian-Morales E et al, in which genotoxic damage was also demonstrated through an increase in MNs and BUDs [24,55].…”
Section: Effect Of Drug Abuse On the Occurrence Of Nuclear Abnormalitiesmentioning
confidence: 82%
“…After the removal of duplicates, 32 were evaluated for the inclusion and exclusion criteria. After careful analysis, 20 articles were included[ 4 5 13 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 ] and after comprehensive evaluation of the titles, abstracts, resulted in the exclusion of 12 articles[ 1 3 9 12 34 35 36 37 38 39 40 41 ] The reason for exclusion was due to incomplete articles, conference abstracts, articles other than the English language, retrospective studies, animal studies, editorial letters, studies on Marijuana and Nargile users and studies on blood and saliva, gingiva and those not following inclusion criteria were excluded, as shown in Figure 1 , according to PICO framework.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the genotoxicity observed in the peripheral lymphocytes from marijuana monousers was compared with those presented in marijuana and tobacco users. While the increase in the formation of γ-H2AX (early biomarker that reflects the formation of double-strand breaks) was present in both groups, the formation of MN was only present in the individuals concomitantly exposed to both agents [10]. Marijuana smoke condensates displayed positive results in the cytokinesis-block micronucleus assay and comet assay in human lung cancer cells with differential p53 expression [11].…”
mentioning
confidence: 99%